Organizational support for strategic development of organizations - Voitenko О. (Ways to Improve Construction Efficiency, 2019)
The article proposes an approach to the organizational support of the organization strategic development using the project management methodology. To ensure the analysis, development and implementation of the organization’s strategy, it is proposed to allocate certain units in its structure: the center of strategic development and the strategic committee. The strategic management functions distributed between these structural units are given. The interaction of the center of strategic development and the strategic committee was proposed. An example of project implementation is described.